Bilayer polarity and its thermal dependency in the e(o) and e(d) phases of binary phosphatidylcholine/cholesterol mixtures - Arrais, Dalila (2007)
Diverse variations in membrane properties are observed in binary phosphatidylcholine/cholesterol mixtures. These mixtures are nonideal, displaying single or phase coexistence, depending on chemical composition and other thermodynamic parameters. When compared with pure phospholipid bilayers, there are changes in water permeability, bilayer thickness and thermomechanical properties, molecular packing and conformational freedom of phospholipid acyl chains, in internal dipolar potential and in lipid lateral diffusion. Based on the phase diagrams for DMPC/cholesterol and DPPC/cholesterol, we compare the equivalent polarity of pure bilayers with specific compositions of these mixtures, by using the Py empirical scale of polarity. Besides the contrast between pure and mixed lipid bilayers, we find that liquid-ordered and liquid-disordered (e(d)) phases display significantly different polarities. Moreover, in the e(o) phase, the polarities of bilayers and their thermal dependences vary with the chemical composition, showing noteworthy differences for cholesterol proportions at 35, 40, and 45 mol%. At 20 degrees C, for DMPC/ cholesterol at 35 and 45 mol%, the equivalent dielectric constants are 21.8 and 23.8, respectively. Additionally, we illustrate potential implications of polarity in various membrane-based processes and reactions, proposing that for cholesterol containing bilayers, it may also go along with the occurrence of lateral heterogeneity in biological membranes. (c) 2007 Elsevier B.V. All rights reserved.